Acacia melanoxylon veneer MWCNT multilayer electromagnetic wave absorbing material and preparation method and application thereof

Through the preparation of the multi-layer electromagnetic wave absorption material of the black wood accosci veneer, combined with the conductive network of CoFe2O4 and MWCNT, the problems of narrow absorption frequency band and poor mechanical properties in drone applications are solved, and efficient electromagnetic wave absorption and excellent mechanics are achieved. It has environmentally friendly and degradable properties, and is suitable for the use of drone structural materials.

CN119300337APending Publication Date: 2025-01-10GUANGXI ZHUANG AUTONOMOUS REGION STATE-OWNED LIUWAN FORESTRY CENT +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411807881.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing electromagnetic wave absorbing materials have problems with narrow absorption frequency bands and poor mechanical properties in drone applications. The traditional materials are thick and high in density, which limits their potential in lightweight applications and do not have environmentally friendly and degradable properties.

Method used

Using the black wood acacia veneer MWCNT multi-layer electromagnetic wave absorption material, ethylene glycol, N,N-dimethylformamide is mixed with carboxylated carbon nanotubes and polyvinylpyrrolidone, ferrous sulfate heptahydrate and sulfuric acid heptahydrate Cobalt forms a metal ion solution, and then is immersed and staggered with the glass fiber layer to form a conductive network of CoFe2O4 and MWCNT, achieving compatibility between wave absorption and mechanical properties.

Benefits of technology

It achieves high electromagnetic absorption strength and broadband absorption performance at a thickness of about 3 mm, has excellent mechanical properties and environmentally friendly and degradable characteristics, is suitable for the application of UAV structural materials, and is simple in preparation and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119300337A_ABST
    Figure CN119300337A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an acacia melanoxylon veneer MWCNT multilayer electromagnetic wave absorbing material, and belongs to the technical field of novel electromagnetic wave absorbing materials.The method comprises the steps that carboxylated carbon nanotubes, polyvinylpyrrolidone, N, N-dimethylformamide and ethylene glycol are evenly mixed and subjected to ultrasonic dispersion, and a solution A is obtained; the method comprises the following steps: weighing ferrous sulfate heptahydrate (FeSO4. 7H2O) and cobaltous sulfate heptahydrate (CoSO4. 7H2O), and dissolving the ferrous sulfate heptahydrate and the cobaltous sulfate heptahydrate into deionized water to obtain a metal ion solution; mixing the solution A with a metal ion solution; a reaction product is obtained after reaction treatment; dipping GFM in the reaction product, taking out and drying to form a GFM layer; and preparing the novel acacia melanoxylon electromagnetic wave absorbing material from the GFM layer and the acacia melanoxylon board in a staggered lamination manner. The preparation method disclosed by the invention has the advantages of simple process, capability of realizing enterprise production, low requirements on synthesis equipment and the like, and the prepared material has excellent broadband wave-absorbing property and excellent mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of microwave absorbing materials, and in particular to a black acacia single-board MWCNT multilayer electromagnetic wave absorbing material having both high-strength and broadband electromagnetic wave absorption, and a preparation method and application thereof. Background Art

[0002] With the development of modern electronic warfare and stealth technology, the demand for electromagnetic wave absorbing materials (MAMs) is growing, especially in the field of unmanned aerial vehicles such as drones. These materials can absorb incident electromagnetic waves (EMW) and convert them into heat or other forms of energy to reduce the electromagnetic signals fed back to the radar, thereby improving the survivability of unmanned aerial vehicles. However, existing electromagnetic wave absorbing materials often have defects such as narrow absorption bandwidth and poor mechanical properties. Especially in drone applications, these materials must not only have wide broadband absorption performance, but also excellent mechanical properties to ensure the stability and reliability of the structure.

[0003] Traditional radar absorbing structures (RAS) are usually made of thick and heavy materials, which not only limits their potential in lightweight applications, but also affects their electromagnetic wave absorption efficiency. For example, Mallesh et al. used nickel-plated glass fiber to prepare RAS with a lightweight folded core, and its effective absorption bandwidth (EAB) reached 3GHz when the structure thickness was 81.6 mm. (See reference 1: S. Mallesh, M. Kim, C. Seok, DJ Hong, M. Kim, J. Hyun, J. Lee, C. Kim, Y. Nam, Folded-core radar-absorbing sandwich composite with sendustparticle-added Ni / plated glass / polyether ether ketone thermoplasticresin in the ultrahigh-frequency band, Compos. Pt. B-Eng. 264 (2023) 110921, https: / / doi.org / 10.1016 / j. compositesb.2023.110921.) Zha et al. constructed a three-layer RAS based on epoxy resin to study the enhanced electromagnetic wave absorption performance of magnetic metal as an intermediate layer. The results show that through a thickness of 8 mm and a density of about 2.4 g / cm 2The structure of EAB has been greatly improved, reaching 6.9 GHz in the frequency range of 2-18 GHz, and the reflection loss (RL) is -54 dB. (See reference 2: H. Zhao, Z. Zhu, Y. Xu, Z. Wang, J. Zhou, Design and preparation of an epoxy resin matrix composite structurewith broadband wave-absorbing properties, Results Phys. 57 (2024) 107353, https: / / doi.org / 10.1016 / j.rinp.2024.107353.) In summary, the electromagnetic wave absorbing structural material as an electromagnetic wave absorbing material shows good electromagnetic wave absorption performance, but its own material thickness and relatively high density greatly limit its application, especially in today's aircraft with extremely high flight performance.

[0004] In addition, today's electromagnetic wave absorbing structural materials often do not have the characteristics of environmental protection and degradability, which is inconsistent with the current requirements of sustainable development. In order to solve this problem, the present invention proposes a multi-layer electromagnetic wave absorbing material based on black wood acacia single board MWCNT, which not only has a wide broadband absorption performance, but also exhibits excellent mechanical properties, and uses environmentally friendly and degradable materials. Summary of the invention

[0005] In view of the above problems, an object of the present invention is to provide a black wood acacia single board MWCNT multilayer electromagnetic wave absorption material, which has excellent wave absorbing performance and mechanical properties while achieving broadband, and realizes perfect compatibility of mechanical properties and wave absorbing performance. The preparation method is simple in process, has low requirements for synthesis equipment and is suitable for industrial mass production.

[0006] The present invention provides a method for preparing a black wood acacia single board MWCNT multilayer electromagnetic wave absorbing material, comprising the following steps: Step 1), ethylene glycol and N,N-dimethylformamide are mixed evenly, and then appropriate amounts of carboxylated carbon nanotubes and polyvinyl pyrrolidone are added to obtain a mixture, and the mixture is crushed by a cell crusher to obtain a solution A; In one embodiment, a certain amount of ethylene glycol (EG) and N,N-dimethylformamide (DMF) are mixed evenly, and then appropriate amounts of carboxylated carbon nanotubes (MWCNT) and polyvinyl pyrrolidone (PVP) are added; the mixture is placed in a cell disruptor and subjected to a disruption treatment for 5 minutes to fully disperse and mix the components to obtain a uniform solution A.

[0007] Step 2), dissolving ferrous sulfate heptahydrate and cobalt sulfate heptahydrate in deionized water to form a metal ion solution; adding the solution A to the incoming ion solution, stirring until the mixture is uniformly mixed to obtain a mixed solution; In one embodiment, a certain amount of deionized water is weighed and placed in a 100 ml beaker, and then ferrous sulfate heptahydrate (FeSO4•7H2O) and cobalt sulfate heptahydrate (CoSO4•7H2O) are added, and the drugs are completely dissolved in the deionized water by stirring to form a metal ion solution; then, solution A prepared in step 1) is slowly added to the metal ion solution, and stirring is continued until the mixture is evenly mixed.

[0008] Step 3), transferring the mixed solution obtained in step 2) to a reaction kettle for reaction treatment to obtain a reaction product; In one embodiment, the mixed solution obtained in step 2) is transferred to a reactor for reaction treatment under the following reaction conditions: temperature 160° C., time 10 h.

[0009] Step 4), immersing the glass fiber layer into the reaction product obtained in step 3) for impregnation treatment; Take a glass fiber layer (GFM) with a size of 50mm*50mm, wash it three times with deionized water to remove surface impurities, and completely immerse it in the reaction product obtained in step 3; through the immersion treatment, the GFM is loaded with the reaction product to prepare for the subsequent lamination process, and a GFM loss layer can be formed after the subsequent lamination. Adjust the loading amount as needed.

[0010] Step 5), the glass fiber layer that has been impregnated in step 4) and the black wood acacia board are prepared by staggered lamination to obtain the black wood acacia single board MWCNT multilayer electromagnetic wave absorption material.

[0011] In one embodiment, the impregnated glass fiber layer and the black wood acacia single board are prepared by staggered lamination to obtain a new black wood acacia single board MWCNT multilayer electromagnetic wave absorbing material; the conditions of the staggered lamination are: pressure 0.5 MPa, temperature 140°C, time 30 min.

[0012] In addition, the thickness and filling degree of the absorbing material structure layer can be adjusted to achieve the regulation of the absorbing performance.

[0013] Furthermore, in step 1), the volume of ethylene glycol is 20 ml, the volume of N,N-dimethylformamide is 20 ml, the mass of polyvinyl pyrrolidone is 2 g, and the mass of carboxylated carbon nanotubes is 0.2 g.

[0014] Furthermore, in step 1), the parameters of the cell disruptor are set as follows: power 600 W, temperature 60 °C, disruption interval 0.5 s (working 0.5 s, pausing 0.5 s, and so on), and total disruption time 5 min. If the power is too high during disruption, the structure of carbon nanotubes will be destroyed, and intermittent operation can reduce this situation.

[0015] Furthermore, in step 2), the mass of cobalt sulfate heptahydrate is 1.5 g, the mass of ferrous sulfate heptahydrate is 1.5 g, and the volume of deionized water is 20 ml.

[0016] Furthermore, in step 3), the reaction conditions of the reactor are: temperature 160°C, time 10 h.

[0017] Furthermore, in step 4), the glass fiber layer has a length and width of 50 mm*50 mm and a thickness of 0.18 mm, and is washed several times with deionized water to remove surface impurities.

[0018] Furthermore, the glass fiber layer is dried after impregnation, and its net weight after drying is 2 to 6 times, preferably 5 times, of the net weight of the glass fiber layer before impregnation. In the actual production process, the loading amount of the glass fiber layer on the reaction product can also be adjusted by impregnation, thereby regulating the electromagnetic wave absorption performance.

[0019] Furthermore, in step 5), the conditions for staggered lamination are: pressure 0.5 MPa, temperature 140°C, time 30 min; from top to bottom, there are black wood acacia board layer, glass fiber layer, black wood acacia board layer, glass fiber layer, black wood acacia board layer, a total of 5 layers, with a total thickness of 3.164 mm, and the thickness of a single black wood acacia board layer is 1 mm.

[0020] The invention provides a black wood acacia single board MWCNT multi-layer electromagnetic wave absorbing material prepared by the preparation method.

[0021] The present invention provides an application of the black wood acacia single board MWCNT multilayer electromagnetic wave absorbing material prepared by the preparation method in aircraft structural materials, specifically, the application of unmanned aerial vehicle structural absorbing materials.

[0022] The present invention has at least the following beneficial effects: 1. Compared with traditional absorbing materials, the black wood acacia single board MWCNT multilayer electromagnetic wave absorbing material prepared by the present invention has a reflection loss value of -30 dB and a bandwidth of 5.6 GHz at a thickness of about 3 mm, achieving high electromagnetic absorption intensity and wide absorption performance at low thickness, and the absorbing performance is adjustable due to the adjustable structural thickness and filling degree.

[0023] 2. The black acacia single-board MWCNT multilayer electromagnetic wave absorbing material prepared by the present invention is based on the black acacia (Acaciamelanoxylon) board, and has the material characteristics of light weight, high strength and hardness, and good stability. After being prepared as an absorbing material, at a thickness of about 3 mm, the tensile strength is 139 MPa, the bending strength is 289.5 MPa, and the bending modulus is 832.3 GPa. It not only has excellent absorbing performance, but also excellent mechanical properties, achieving perfect compatibility between mechanical properties and absorbing performance.

[0024] 3. The preparation method of the present invention is to first prepare an impregnated GFM loss layer, and then press it with a black wood acacia board. The preparation method is simple, the preparation process is simple, and no complex synthesis equipment is required, and large-scale mass production can be carried out.

[0025] 4. Since the loss layer is a conductive network formed by CoFe2O4 and MWCNT, the generation of interface polarization absorbs a large amount of electromagnetic waves. In addition, the conductive network increases the conductivity loss, further enhancing the absorption of electromagnetic waves.

[0026] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The X-ray diffraction pattern of the lossy layer of Example 1 of the present invention is Figure 2 This is a SEM photograph of the lossy layer of Example 1 of the present invention; Figure 3 This is an electronic image of the multilayer structure of the Acacia nigra single-plate MWCNT multilayer electromagnetic wave absorbing material prepared in Example 1 of the present invention; Figure 4 This is a reflection loss spectrum of the Acacia nigra single-plate MWCNT multi-layer electromagnetic wave absorbing material prepared in Example 1 of the present invention; Figure 5 The tensile test load-displacement curve of the Acacia nigra single-sheet MWCNT multi-layer electromagnetic wave absorbing material prepared in Example 1 of the present invention; Figure 6 The load-displacement curve of the three-point bending test of the Acacia nigra single-sheet MWCNT multi-layer electromagnetic wave absorbing material prepared in Example 1 of the present invention; Figure 7 Comparison of reflection loss diagrams of multilayer electromagnetic wave absorbing materials with different loads of the present invention. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0029] Example 1 A method for preparing a black wood acacia single board MWCNT multilayer electromagnetic wave absorbing material, comprising the following steps: Step 1: Preparation of Solution A A certain amount of ethylene glycol (EG) and N,N-dimethylformamide (DMF) were mixed evenly, and then appropriate amounts of carboxylated carbon nanotubes (MWCNT) and polyvinyl pyrrolidone (PVP) were added; the mixture was placed in a cell disruptor and subjected to disruption for 5 minutes to obtain a uniform solution A. In this embodiment, the volume of DMF was 20 ml, the volume of EG was 20 ml, the mass of PVP was 2 g, the mass of MWCNT was 0.2 g, and the parameters of the cell disruptor were set as follows: power 600 W, temperature 60 ° C, disruption interval 0.5 s (working 0.5 s, pausing 0.5 s, and so on), and the total disruption time was 5 min.

[0030] Step 2: Preparation and mixing of metal ion solutions Weigh a certain amount of deionized water and place it in a 100ml beaker, then add ferrous sulfate heptahydrate (FeSO4•7H2O) and cobalt sulfate heptahydrate (CoSO4•7H2O), stir to completely dissolve the drugs in the deionized water to form a metal ion solution; then, slowly add the solution A prepared in step 1 to the metal ion solution, and continue to stir until the mixture is uniform. In this embodiment, the mass of CoSO4·7H2O is 1.5 g, the mass of FeSO4·7H2O is 1.5 g, and the volume of deionized water is 20ml.

[0031] Step 3: Reaction processing The mixed solution obtained in step 2 was transferred to a 100 ml reactor for reaction treatment. The reaction conditions of the reactor were: temperature 160 °C, time 10 h.

[0032] Step 4: Impregnation of GFM Take a piece of GFM (glass fiber layer) with a length and width of 50mm*50mm and a thickness of 0.18mm, wash it three times with deionized water to remove surface impurities, and completely immerse it in the reaction product obtained in step 3 for 5-6 seconds to obtain an impregnated GFM, and then dry it to form a GFM layer. (After measurement, the net weight of the impregnated GFM after drying is 5 times that of the GFM). Through the impregnation treatment, the GFM is loaded with the reaction product to prepare for the subsequent lamination treatment. After the subsequent lamination treatment, the impregnated GFM can form a GFM loss layer.

[0033] Step 5: Lamination preparation of new black wood acacia single board MWCNT multilayer electromagnetic wave absorption material The impregnated GFM layer and the black acacia veneer (thickness 1 mm) were cross-laminated to prepare a new black acacia veneer MWCNT multilayer electromagnetic wave absorbing material. In this embodiment, the cross-lamination conditions are: pressure 0.5 MPa, temperature 140 ° C, time 30 min, from top to bottom, the black acacia board layer, glass fiber layer (loss layer), black acacia board layer, glass fiber layer (loss layer), black acacia board layer, a total of 5 layers, with a total thickness of 3.164 mm; the glass fiber layer (loss layer) and the black acacia board layer are tightly combined and cross-laminated, and their structure and thickness are as follows Figure 3 shown.

[0034] Figure 1 As shown, it is the X-ray diffraction pattern of the loss layer of Example 1 of the present invention, and it can be seen that it is a typical X-ray diffraction pattern of CoFe2O4 / MWCNT.

[0035] like Figure 2 This is a SEM photograph of the lossy layer prepared in Example 1 of the present invention. It can be seen that the glass fiber has a diameter and thickness of about 7.5 um, and the outside of the fiber is coated with a uniform CoFe2O4 / MWCNT electromagnetic wave absorbing material.

[0036] Figure 3 The multilayer structure diagram and measured thickness of the black acacia electromagnetic wave absorbing material prepared in Example 1 of the present invention; it can be seen that the black acacia board and the lossy layer are tightly combined and staggered to form a five-layer plywood with a thickness of 3.164 mm.

[0037] Figure 4 This is the reflection loss spectrum of the new Acacia amurense electromagnetic wave absorbing material prepared in Example 1 of the present invention; it can be seen that the material exhibits excellent wave absorbing performance, with a reflection loss value of -30 dB and a bandwidth of 5.6 GHz.

[0038] Figure 5 This is the tensile test load-displacement curve of the new Acacia nigra electromagnetic wave absorbing material prepared in Example 1 of the present invention. It is calculated by the formula that the material has excellent tensile strength, and the tensile strength is 139 MPa.

[0039] Figure 6 This is the load-displacement curve of the three-point bending test of the new black wood acacia electromagnetic wave absorbing material prepared in Example 1 of the present invention. It is calculated by the formula that the material has excellent bending strength and bending modulus, with a bending strength of 289.5 MPa and a bending modulus of 832.3 GPa.

[0040] In this Example 1, the dry net weight of the impregnated GFM is 5 times that of the GFM, and the Acacia nigra single-plate MWCNT multilayer electromagnetic wave absorbing material is prepared, represented by 500.

[0041] For comparison, according to the method of Example 1, step 4 is modified as follows: the dry net weight of the impregnated GFM is 3 times that of the GFM, and the black wood acacia single board MWCNT multilayer electromagnetic wave absorbing material is prepared, represented by 300.

[0042] and, preparing the unimpregnated GFM, and similarly preparing the black wood acacia multilayer electromagnetic wave absorbing material, represented by 0; Comparing the reflection loss of the above materials, the results are as follows Figure 7 As shown, the black wood acacia single board MWCNT multilayer electromagnetic wave absorption material-500 prepared in this embodiment 1 has higher electromagnetic absorption intensity.

[0043] The preparation method of the invented new black acacia single board MWCNT multilayer electromagnetic wave absorption material is to prepare an impregnated loss layer, and then press it with the black acacia board. The preparation method is simple. Since the loss layer is a conductive network formed by CoFe2O4 and MWCNT, the generation of interface polarization absorbs a large amount of electromagnetic waves, and the conductive network increases the conductivity loss, further enhancing the absorption of electromagnetic waves. The preparation method of the present invention has the advantages of simple process, large output and low requirements for synthesis equipment, and can be used for large-scale industrial production. The prepared black acacia single board MWCNT multilayer electromagnetic wave absorption material has good mechanical properties and good wave absorption performance, and is very suitable for use as an electromagnetic wave absorption material for drone structures.

[0044] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and the embodiments. They can be applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily realized.

Claims

1. A method for preparing a black wood acacia single board MWCNT multilayer electromagnetic wave absorbing material, characterized in that: The following steps are involved: Step 1), ethylene glycol and N,N-dimethylformamide are mixed evenly, and then appropriate amounts of carboxylated carbon nanotubes and polyvinyl pyrrolidone are added to obtain a mixture, and the mixture is crushed by a cell crusher to obtain a solution A; Step 2), dissolving ferrous sulfate heptahydrate and cobalt sulfate heptahydrate in deionized water to form a metal ion solution; Adding the solution A to the incoming ion solution, stirring until the mixture is uniform to obtain a mixed solution; Step 3), transferring the mixed solution obtained in step 2) to a reaction kettle for reaction treatment to obtain a reaction product; Step 4), immersing the glass fiber layer into the reaction product obtained in step 3) for impregnation treatment; Step 5), the glass fiber layer that has been impregnated in step 4) and the black wood acacia board are prepared by staggered lamination to obtain the black wood acacia single board MWCNT multilayer electromagnetic wave absorption material.

2. The method for preparing the Acacia nigra single-plate MWCNT multi-layer electromagnetic wave absorbing material according to claim 1, characterized in that: In step 1), the volume of ethylene glycol is 20 ml, the volume of N,N-dimethylformamide is 20 ml, the mass of polyvinyl pyrrolidone is 2 g, and the mass of carboxylated carbon nanotubes is 0.2 g.

3. The method for preparing the Acacia nigra single-plate MWCNT multi-layer electromagnetic wave absorbing material according to claim 2, characterized in that: In step 1), the parameters of the cell disruptor were set as follows: power 600 W, temperature 60 °C, disruption interval 0.5 s, and total disruption time 5 min.

4. The method for preparing the Acacia nigra single-plate MWCNT multi-layer electromagnetic wave absorbing material according to claim 2, characterized in that: In step 2), the mass of cobalt sulfate heptahydrate is 1.5 g, the mass of ferrous sulfate heptahydrate is 1.5 g, and the volume of deionized water is 20 ml.

5. The method for preparing the Acacia nigra single-plate MWCNT multi-layer electromagnetic wave absorbing material according to claim 2, characterized in that: In step 3), the reaction conditions of the reactor are: temperature 160°C, time 10 h.

6. The method for preparing the Acacia nigra single-plate MWCNT multi-layer electromagnetic wave absorbing material according to claim 2, characterized in that: In step 4), the glass fiber layer has a length and width of 50 mm*50 mm and a thickness of 0.18 mm, and is washed several times with deionized water to remove surface impurities.

7. The method for preparing the Acacia nigra single-plate MWCNT multi-layer electromagnetic wave absorbing material according to claim 2 or 6, characterized in that: The impregnated glass fiber layer is dried, and the net weight after drying is 5 times the net weight of the glass fiber layer before impregnation.

8. The method for preparing the Acacia nigra single-plate MWCNT multi-layer electromagnetic wave absorbing material according to claim 6, characterized in that: In step 5), the conditions for staggered lamination are: pressure 0.5 MPa, temperature 140°C, time 30 min; from top to bottom, there are 5 layers in total: black wood acacia board layer, glass fiber layer, black wood acacia board layer, glass fiber layer, and black wood acacia board layer.

9. A black wood acacia single board MWCNT multilayer electromagnetic wave absorption material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the Acacia nigra single sheet MWCNT multilayer electromagnetic wave absorbing material prepared by the preparation method according to any one of claims 1 to 8 in aircraft structural materials.

Citation Information

Cited By

  • Preparation method of multifunctional composite coating on metal surface

    CN120623821A